MIGRATION AND EDUCATION: AN APPROACH TO HAITIAN INCLUSION IN THE CHILEAN EDUCATIONAL SYSTEM (Revista Espacio Regional, 2020)
The present essay situates the phenomenon of Haitian migration within the framework of the educational system in Chile. For this, contextual elements of the country of departure and the country of entry are observed. An approach to education as an inclusive element is carried out and the concepts of multiculturalism and interculturality are discussed. The conclusions indicate that it is necessary to carry out further studies on the political guidelines in education on this subject, specifically, on methodologies pointing towards the inclusion of the migrant population.